IDENTIFIKASI TINGKAT KESULITAN BELAJAR FISIKA POKOK BAHASAN GERAK PADA SISWA KELAS VII SMP NEGERI 13 MATARAM - Muhaemin Muhaemin (Lensa: Jurnal Kependidikan Fisika, 2014)
The study aims to describe the types of learning difficulties and their presentations on the subject of "motion". The sample in this research is the second grade students at secondary high school as much as 2 (two) classes. The data that has been analyzed is the percentage of student error. The results indicated that the types of learning difficulties experienced are: difficulty to understand concepts, reading and understanding graphs, analyzing problems, using formulas, and calculations. The level of learning difficulties on the subject of "motion" from sub-subjects difficult to the easiest are: Straight-Changed Motion (50.64%), velocity and speed (44.01%), Regular Straight Motion (43.87%) and Position and Displacement (35.08%). The average of students' learning difficulty is (43.40%). We conclude that many students have difficulty learning on the subject of Motion.